Antecedents to cognitive business model evaluation: a dynamic managerial capabilities perspective - Tim Heubeck; Reinhard Meckl (Review of Managerial Science, 2021)
The increasing misalignment between the technological and economic domains in today's digitalized global economy puts managers under constant pressure to redesign firms' business models. Business model innovation has thus become a critical managerial challenge to develop and sustain competitive advantages. Building on the dynamic managerial capabilities perspective, we argue that managers are at the heart of strategic change through business model innovation. We hypothesize that decision-making regarding business model innovation is the outcome of how managers cognitively process information. We further reason that while managerial human capital and social capital reinforce each other, they also promote managers' ability to consciously evaluate options for business model innovation. Our empirical study builds on a sample of firms operating primarily within the Industry 4.0 sector. The results significantly confirm managerial human and social capital as two crucial antecedents to cognitive business model innovation. Contrary to the literature, the data set does not show a significant positive relationship between managerial human and social capital. Our main contributions to the literature are twofold; from a methodological perspective, we are one of the first to construct a multidimensional measurement of dynamic managerial capabilities, while from a theoretical and practical perspective, our findings further underline the relevance of dynamic managerial capabilities for business model innovation. Finally, we discuss theoretical and practical implications and propose future avenues for research.
Keywords: H15; H20; H25; J05; C12; L26; M12; O31; O32; O33; 650; Business model innovation; Dynamic managerial capabilities; Human capital; Managerial cognition; Organizational change; Social capital